Ultra-Low-Voltage Frequency Synthesizer and Successive-Approximation Analog-to-Digital Converter for Biomedical Applications - Hung, Chung-Chih.; Wang, Shih-Hsing.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book introduces the origin of biomedical signals and the operating principles behind them and presents the characteristics of common biomedical signals for subsequent signal measurement and judgment. Since biomedical signals are captured by wearable devices, sensor devices, or implanted devices, these devices are all battery-powered to maintain long working time. We hope to reduce their power consumption to extend service life, especially for implantable devices, because battery replacement can only be done through surgery. Therefore, we must understand how to design low-voltage low-power integrated circuits. Provides necessary background information on biomedical signals and proceeds with design considerations for low supply voltage analog circuits; Describes design techniques for not only frequency synthesizers and ADCs, but also the ultra-low voltage design techniques of these circuits; Demonstrates examples to overcome typical design challenges. .
1. Introduction to biomedical signals and their applications -- 2. Low-power and low-voltage VLSI Circuit design Techniques for Biomedical Applications -- 3. Introduction of Frequency Synthesizer -- 4. A 0.35-V 240-(So(BW Fast-Lock and Low-Phase-Noise frequency synthesizer for implantable biomedical applications -- 5. Introduction of ADC -- 6. A 0.3V 10b 3MS/s SAR ADC with comparator calibration and kickback noise reduction for biomedical applications -- 7. Summary.s
Keywords: Electronic circuits; Telecommunication; Electronics; Electronic Circuits and Systems; Microwaves, RF Engineering and Optical Communications; Electronics and Microelectronics, Instrumentation; Biomedical Engineering -- instrumentation; Analog-Digital Conversion; Micro-Electrical-Mechanical Systems -- instrumentation; Biosensing Techniques -- instrumentation; Signal Processing, Computer-Assisted -- instrumentation